A DESIGN FOR A MECHANISM TO DEVELOP STUDENTS’ CONCEPTUAL THINKING IN THE HIGHER EDUCATION PROCESS - Gofurova Barnoxon (International Scientific and Current Research Conferences, 2025)
This article provides a scientific-theoretical and practical justification for designing a mechanism to develop students’ conceptual thinking in higher education institutions. Conceptual thinking is interpreted as a type of intellectual activity that forms students’ competencies in systematizing knowledge, identifying interconceptual relationships, making well-grounded decisions in problem situations, and conducting reflective analysis. The study systematizes the structural stages, pedagogical conditions, and methodological tools for designing a mechanism to develop conceptual thinking. As a result, an integrative pedagogical model aimed at developing conceptual thinking and criteria for evaluating its effectiveness were developed.